Continuous, Lateralized Auditory Stimulation Biases Visual Spatial Processing - Pomper, Ulrich; Schmid, Rebecca; Ansorge, Ulrich (Frontiers in Psychology, 2020)
Sounds in our environment can easily capture human visual attention. Previous studies have investigated the impact of spatially localized, brief sounds on concurrent visuospatial attention. However, little is known on how the presence of a continuous, lateralized auditory stimulus (e.g., a person talking next to you while driving a car) impacts visual spatial attention (e.g., detection of critical events in traffic). In two experiments, we investigated whether a continuous auditory stream presented from one side biases visual spatial attention toward that side. Participants had to either passively or actively listen to sounds of various semantic complexities (tone-pips, spoken digits, a spoken story) while performing a visual target discrimination task. During both passive and active listening, we observed faster response times to visual targets presented spatially close to the relevant auditory stream. Additionally, we found that higher levels of semantic complexity of the presented sounds led to reduced visual discrimination sensitivity, but only during active listening to the sounds. We provide important novel results by showing that the presence of a continuous, ongoing auditory stimulus can impact visual processing, even when the sounds are not endogenously attended to. Together, our findings demonstrate the implications of ongoing sounds on visual processing in everyday scenarios such as moving about in traffic.